Nanostructure of thermally aged thermoplastic polyurethane and its evolution under strain. (August 2016) - Li, Xuke; Stribeck, Almut; Schulz, Imke; Pöselt, Elmar; Eling, Berend; Hoell, Armin
Graphical abstract: Highlights: The variation of the morphology of unaged and aged TPU is monitored in situ during tensile tests by SAXS. The variation of the hard-domain volume fraction is computed. The main elongation mechanism is destruction of hard domains. Hard domains of unaged material are rigid. Hard domains of aged material appear softened. Abstract: A polyether based thermoplastic polyurethane (TPU) containing 43 wt.% hard domains is aged in air at 150 °C for 15 and 36 days, respectively. Straining of the samples (0 d, 15 d, 36 d) is monitored by small-angle X-ray scattering (SAXS). Visual inspection of the chord distribution functions (CDFs) guides to a model for the fitting of the longitudinal projection of the fiber scattering. This model comprises two components: isolated hard domains (solos) and hard domains which are arranged with respect to a next neighbor (duos). Aging increases the average size of the hard domains (HD) (0 d:5, 15 d:8, 36 d:7 nm) and the average distance between them (0 d:3, 15 d:6, 36 d:9 nm). It decreases the volume fraction of HD considerably. The probable mechanism is selective degradation of the smaller hard domains. With increasing strain the relative loss of HD is the same for all samples. Aging softens the HDs. Softened HDs lengthen when the sample is stretched. They are destroyed before the rigid ones. HD-lengthening is identical for sample 15 d and 36 d. Only with the aged materials small strain causes HDs to migrate from the random to the arranged component – and back at higher strain. Sample 36 d breaks at strain 1.5, whereas sample 15 d resists. Here the soft-domain height doubles suddenly at strain 1.2. The indicated mechanism is disruption of each second HD.